"Betwixt and Between": Leisure-time Teachers and the Construction of Professional Identities. Issue 6 (19th September 2019) - Ackesjö, Helena; Lindqvist, Per; Nordänger, Ulla Karin
ABSTRACT: In 2014, a newly formed group of teachers graduated from Swedish universities. In addition to their qualification as leisure-time pedagogues, their degree includes teaching practical/aesthetical subjects in compulsory school. This group of teachers thus has to relate to dual professional identities and to maintain a balance between the socially oriented leisure-time centres and a goal- and results-driven school. In this article we describe their first two years after graduation, trying to get hold of their negotiation of professional identities and orientation in the professional landscape. Results shows that the graduates try to balance own ideals and hybrid professional intentions against traditional professional identities and labour market conditions and that position in a liminal phase might be crucial for the outcome.